Creation of virtual channels in the retina using synchronous and asynchronous stimulation—a modelling study. (11th November 2020) - Song, Xiaoyu; Guo, Tianruo; Shivdasani, Mohit N; Dokos, Socrates; Lovell, Nigel H; Li, Xinxin; Qiu, Shirong; Li, Tong; Zheng, Shiwei; Li, Liming
Abstract: Objective. The spatial resolution of an implantable neural stimulator can be improved by creation of virtual channels (VCs). VCs are commonly achieved through synchronized stimulation of multiple electrodes. It remains unknown whether asynchronous stimulation is able to generate comparable VC performance in retinal stimulation, and how VC can be optimized by re-designing stimulation settings. This study begins with exploring the feasibility of creating VCs using synchronous and asynchronous epiretinal stimulation, and ending with predicting the possible VC performance with a thorough exploration of stimulation parameter space. Approach. A computational model of epiretinal dual-electrode stimulation is developed to simulate the neural activity of a population of retinal ganglion cells (RGCs) under both synchronous and asynchronous stimulation conditions. The interaction between the electrode and RGCs under a range of stimulation parameters are simulated. Main results. Our simulation based on direct RGC activation suggests that VCs can be created using asynchronous stimulation. Two VC performance measures: 1) linearity in the change in centroid location of activated RGC populations, and 2) consistency in the size of activated RGC populations, have comparable performance under asynchronous and synchronous stimulation with appropriately selected stimulation parameters. Significance. Our findings support the possibility of creating VCs by directly activating RGCs under synchronous and asynchronous stimulation conditions. This study establishes the fundamental capability of VC creation based on temporal interactions within the RGC population alone and does not include the effects of potential indirect activation of any surviving inner retinal network neurons. Our results provide theoretical evidence for designing next-generation retinal prosthesis with higher spatial resolution.